Corporate governance, firm characteristics, external environment and performance of financial institutions in Uganda: A review of literature - Juliet Wakaisuka-Isingoma; Josiah Aduda; Gituro Wainaina; Cyrus Iraya Mwangi (Cogent Business & Management, 2016)
Main Objective of the Study: Examine the relationship among corporate governance, firm characteristics, external environment, and performance of financial institutions in Uganda. Value of the Study: The paper is expected to create value to different categories of groups like: the central bank, as a regulatory body; financial institutions that can benchmark with the views of different scholars; the public can make suitable decisions regarding choices where to bank and borrow; the academia in terms of research; and the government in terms of planning, policy formulation, and budgeting for the country. The paper is expected to make significant contributions to theory building by affirming to current theories. The paper made policy recommendations aimed at enhancing firm performance within the sector, given the magnitude of corporate governance, firm characteristics, and the external environment. The paper provided a different perspective of understanding firm performance of financial institutions by integrating, the agency theory, resource dependence theory, transaction cost theory, and the stakeholder theory. Theoretical Foundation: Agency theory, transaction cost theory, stakeholder theory, and resource dependency theory.
Keywords: 650